Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.